Cost-effectiveness of continuous positive airway pressure therapy for obstructive sleep apnea: health care system and societal perspectives. Issue 12 (12th August 2019) - Streatfeild, Jared; Hillman, David; Adams, Robert; Mitchell, Scott; Pezzullo, Lynne
Abstract: Study Objectives: To determine cost-effectiveness of continuous positive airway pressure (CPAP) treatment of obstructive sleep apnea (OSA) in Australia for 2017–2018 to facilitate public health decision-making. Methods: Analysis was undertaken of direct per-person costs of CPAP therapy (according to 5-year care pathways), health system and other costs of OSA and its comorbidities averted by CPAP treatment (5-year adherence rate 56.7%) and incremental benefit of therapy (in terms of disability-adjusted life years [DALYs] averted) to determine cost-effectiveness of CPAP. This was expressed as the incremental cost-effectiveness ratio (= dollars per DALY averted). Direct costs of CPAP were estimated from government reimbursements for services and advertised equipment costs. Costs averted were calculated from both the health care system perspective (health system costs only) and societal perspective (health system plus other financial costs including informal care, productivity losses, nonmedical accident costs, deadweight taxation and welfare losses). These estimates of costs (expressed in US dollars) and DALYs averted were based on our recent analyses of costs of untreated OSA. Results: From the health care system perspective, estimated cost of CPAP therapy to treat OSA was $12 495 per DALY averted while from a societal perspective the effect was dominant (−$10 688 per DALY averted) meaning it costs more not to treat the problem than to treat it. Conclusions: These estimates suggest substantial community investment in measures to more systematically identify and treat OSA is justified. Apart from potential health and well-being benefits, it is financially prudent to do so.